Intra-articular injection of monoiodoacetate induces diverse hip osteoarthritis in rats, depending on its dose - Satoshi Yoh; Yuya Kawarai; Shigeo Hagiwara; Sumihisa Orita; Junichi Nakamura; Shuichi Miyamoto; Takane Suzuki; Tsutomu Akazawa; Yuki Shiko; Yohei Kawasaki; Seiji Ohtori (BMC Musculoskeletal Disorders, 2022)
Abstract Background Monoiodoacetate (MIA)-induced arthritis models are used widely in osteoarthritis (OA) research to develop effective conservative treatments for hip OA, as an alternative to joint replacement surgery. In joint OA models, such as the MIA-induced knee OA model, various doses of MIA are utilized, depending on the purpose of the research. So far, only 2 mg of MIA has been used for MIA-induced hip OA research. We hypothesized that the amount of MIA should be adjusted according to the osteoarthritis model under investigation. We performed radiographic and histological evaluations in rats for hip OA models induced by different doses of MIA. Methods One hundred and eighty right hips of six-week-old, male Sprague–Dawley rats (n = 30 rats per group) were treated with either a single intra-articular injection of various doses of MIA (0.25, 0.5, 1.0, 2.0, and 4.0 mg) dissolved in 25 μl of sterile saline (MIA group), or with 25 μl of sterile saline alone (Sham group). Radiographic and histological evaluations of the hip joint were performed at one, two, four, eight, and 12 weeks after administration (n = 6 rats per group per time point). Results OA changes progressed from 1 week after administration in the 1.0-mg, 2.0-mg, and 4.0-mg MIA groups. The degree of OA changes increased as the dose of MIA increased. The 0.25-mg and 0.5-mg MIA groups presented fewer OA changes than the 2.0-mg and 4.0-mg MIA groups during the entire study period (up to 12 weeks). The administration of 0.25 mg and 0.5 mg of MIA-induced both radiographic and histological OA changes in a time-dependent manner, whereas more than 2 mg of MIA provoked end-stage OA at 8 weeks after injection. Absolute, dose-dependent histopathological OA changes were observed 4 weeks after MIA administration. Conclusions Intra-articular MIA injection to the hip joints of rats induced diverse OA changes dose-dependently. Research for developing novel conservative treatments for hip OA and intractable pain should consider the pathological condition when determining the dose of MIA to be employed.